2006
DOI: 10.1308/003588406x149174
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerve Neuromodulation for the Treatment of Lower Bowel Motility Disorders

Abstract: INTRODUCTION Incontinence and constipation are common and cause a high degree of physical, social and psychological impairment. Maximal conservative therapy may improve some patients but many remain symptomatic. Surgical options are often unsatisfactory, with variable result and further options are limited. Sacral nerve stimulation uses electrical stimulation applied to the sacral nerves, eliciting a physiological effect on the lower bowel, anal sphincter and pelvic floor, resulting in clinical benefit. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 20 publications
1
29
0
7
Order By: Relevance
“…This modulation of afferent and autonomic pathways may also explain why SNS may be effective for slow transit constipation and rectal urgency. 11 PNTML is often measured in patients with fecal incontinence. It is a controversial measure, and a pudendal nerve trace can be difficult to elicit, even in patients without fecal incontinence, and it has a high interobserver variation.…”
Section: Discussionmentioning
confidence: 99%
“…This modulation of afferent and autonomic pathways may also explain why SNS may be effective for slow transit constipation and rectal urgency. 11 PNTML is often measured in patients with fecal incontinence. It is a controversial measure, and a pudendal nerve trace can be difficult to elicit, even in patients without fecal incontinence, and it has a high interobserver variation.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in comorbid pelvic pain and bowel symptoms 1,2 after sacral and more recently, chronic pudendal neuromodulation for voiding complaints 3,4 have already been observed. Studies have also reported encouraging results after treating fecal incontinence (FI), 5 constipation, 6,7 irritable bowel syndrome (IBS), 8 and anorectal pain 9 with neuromodulation.…”
Section: Introductionmentioning
confidence: 99%
“…The precise pathophysiological mechanism why the procedure is effective is unknown, and this may be seen in the medical literature for a variety of anorectal manometry values, both pre-and post-operatively, where various irreproducible effects are described for all series: increased maximum tolerated volume, increased volume at which sensation takes place, and increased sphincter resting pressure (18)(19)(20)(21). In our study, following the procedure we saw that voluntary contraction pressure improved in a statistically significant manner.…”
Section: Discussionmentioning
confidence: 55%